2020
DOI: 10.3390/diagnostics10080564
|View full text |Cite
|
Sign up to set email alerts
|

Two Reliable Methodical Approaches for Non-Invasive RHD Genotyping of a Fetus from Maternal Plasma

Abstract: Noninvasive fetal RHD genotyping is an important tool for predicting RhD incompatibility between a pregnant woman and a fetus. This study aimed to assess a methodological approach other than the commonly used one for noninvasive fetal RHD genotyping on a representative set of RhD-negative pregnant women. The methodology must be accurate, reliable, and broadly available for implementation into routine clinical practice. A total of 337 RhD-negative pregnant women from the Czech Republic region were tested in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Most laboratories that provide noninvasive cffDNA RHD genotyping perform a real-time PCR test for the presence or deletion of the RHD gene. Our previous study confirmed that for the Czech population RhD negativity is almost exclusively associated with the deletion of the entire RHD gene [26].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most laboratories that provide noninvasive cffDNA RHD genotyping perform a real-time PCR test for the presence or deletion of the RHD gene. Our previous study confirmed that for the Czech population RhD negativity is almost exclusively associated with the deletion of the entire RHD gene [26].…”
Section: Discussionsupporting
confidence: 85%
“…RHD tests using real-time PCR and RHCE and KEL using minisequencing have already been introduced at our workplace [ 26 , 27 , 28 ]. One of the aims of the study was to methodically unify both procedures and, in the case of RHCE and KEL , to simplify and speed up the examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, maternal anti-RhD IgG antibodies (anti-D) that cross the placenta and destroy fetal red blood cells cause anemia in the infant (RBCs). This is referred to as (HDN) [63].…”
Section: Real-time Pcr-applied Biosystemsmentioning
confidence: 99%